Carbon Nanotubes: An Optimistic Nanomaterial with Superfluity Characteristics in Drug Delivery for the Treatment of Arthritis - Srinivasan, Venkataramanan; Palanisamy, Ponnusamy (Indian Journal of Pharmaceutical Education and Research, 2022)
Arthritis is chronic disease that affects the joint system and induces pain and inflammation in human body. Nanotechnology based drug delivery has progressed to be viable and more attractive for the treatment of arthritis. A carbon nanotube is one of the foremost prominent nanomaterials with high surface area utilized to exhibit stable release of drugs. Nonetheless, researchers have done investigations using either single-walled carbon nanotubes (SWCNT) or multi-walled carbon nanotubes (MWCNT) to gain optimistic results in targeted delivery for arthritis disorder. In this view, functionalized carbon nanotubes are employed to deliver drugs with higher accuracy and controlled release of drugs with less toxic effects. Unfortunately, very limited investigations are reported the prospective utilization of functionalized carbon nanotubes as eminent drug carriers for arthritis treatment. Moreover, the amounts of toxicity of carbon nanotubes, as well as their aggregation in cells and tissues are the key limits that must be considered evidently. The biosafety exposure of carbon nanotubes to humans are still a source of concern. As a result, more research is needed to solve the obstacles associated with carbon nanotubes in conjugation with drugs such as agglomeration, lack of solubility and interaction mechanism with drugs. In this review, we discussed the significant characteristics and outcomes of carbon nanotubes in drug delivery for the treatment of arthritis disease. The toxic level of carbon nanotubes is projected and why the incorporation of CNTs in drug delivery is still limited in various phases is highlighted. The biosafety aspects, cellular uptake mechanism and the importance of functionalization carbon nanotubes in drug delivery are reviewed.
Keywords: Arthritis; Drug delivery system; Single-walled carbon nanotube; Toxicity; Multi- walled carbon nanotube; Nanoparticles